Signs in the intersemiotic reading of Adriana Varejão’s work - Costa, Marcia; Teixeira, Níncia Cecília Ribas Borges (The ESPecialist, 2024)
With the arrival of Cultural Studies, many opportunities were opened to explore previously elitized spaces, such as academia, art, and culture itself. Minorities are now gaining visibility, producing, and consuming products that were previously restricted. With this, various minority classes, such as women, can show and develop their academic, artistic, and cultural works, crossing canonical borders and enabling discourses from the most varied social spheres. For this research, we focused our analysis on the theory of Intersemiotic Translation, in which one materiality converts into another, in our case, transposing the plastic arts to the text, using a study based on signs and their symbologies. The research verifies through signs, in the Works Ama Divers, of Adriana Varejão, themes related to women.